2022
DOI: 10.1039/d1ra05382e
|View full text |Cite
|
Sign up to set email alerts
|

Polymer grafted magnetic graphene oxide as a potential nanocarrier for pH-responsive delivery of sparingly soluble quercetin against breast cancer cells

Abstract: Polymer grafted magnetic graphene oxide (GO–PVP–Fe3O4) as an efficient nanocarrier for the delivery of anticancer drug quercetin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 44 publications
(54 reference statements)
0
14
0
Order By: Relevance
“…These results confirmed that GO-based materials exhibited a good sustainable release profile, because of which they can be used as a drug delivery system. This can be adequate to achieve a desirable local concentration release of the drugs during the initial few hours [ 59 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…These results confirmed that GO-based materials exhibited a good sustainable release profile, because of which they can be used as a drug delivery system. This can be adequate to achieve a desirable local concentration release of the drugs during the initial few hours [ 59 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…229,230 In 2022, polymer-grafted magnetic GO (GO-PVP-Fe 3 O 4 ) was successfully developed and employed in anticancer drug delivery. 231 GO was first functionalized with polyvinylpyrrolidone (PVP) before being implanted with magnetic nanoparticles (Fe 3 O 4 ) using a simple and efficient chemical process. Noncovalent interactions were used to load an anticancer drug quercetin (QSR) on GO-PVP-Fe 3 O 4 , as shown in Figure 31.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“… Schematic representation of the synthesis of magnetic GO and drug loading on magnetic GO. Reproduced with permission from ref ( 248 ). Copyright @2022, Royal Society of Chemistry, Royal Society of Chemistry Advances.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…Nanocomposites fabricated by functionalization of GO with polyvinylpyrrolidone (PVP) and then grafted with Fe 3 O 4 NPs loaded with quercetin exhibited pH-responsive controlled drug release and biocompatibility to non-tumorigenic epithelial HEK 293T cells, with higher toxicity to MDA MB 231 human breast cancer cells than free quercetin. Moreover, targeted drug delivery using this magnetic GO nanocomposite can be controlled by an external magnetic field [ 147 ]. Fe 3 O 4 −GO nanohybrids coated with β-cyclodextrin−cholic acid−hyaluronic acid polymer, characterized with multiple-targeted features (the cholic acid supplied the hepatic target, CD44-receptor target of hyaluronic acid, and magnetic target of Fe 3 O 4 ), exhibited local chemo-photothermal synergistic effects via directly generated apoptosis of hepatocellular carcinoma cells, trigging the release of encapsulated camptothecin, resulting in a tumor inhibition rate >90%; this nanohybrid could be used for enhanced liver tumor therapy [ 148 ].…”
Section: Gbns As Drugs and Nanocarriersmentioning
confidence: 99%